The Prevention of Spontaneous Combustion in the South Yorkshire Area - E. L. Evans (The Institute of Materials, Minerals and Mining, 1905)
The historical development of South Yorkshire mining is traced and note made of the liability to generate spontaneous combustion of some of the seams which have been worked. The liability factor is analysed firstly as an inherent property in the material of a coal seam, and secondly as a circumstance of a situation in which access is provided for the air necessary to sustain oxidation. The geological settings in which incidents of heatings have been known to occur is discussed and conditions favouring a natural pre-disposition to spontaneous oxidation exposed, particularly the effect of argillaceous material overlying the seam. An extensive strata-dynamic study follows to demonstrate the situations in which stray air currents tend to impinge on readily oxidizable material. Prevention techniques are indicated as the identification of strata-dynamic situations in which air access to broken coal is induced and thereafter th operational action to seal off the voids which have been opened up so as to exclude air from the broken coal. Measures to reduce the tendency for ventilating air to short circuit across waste voids, and to obviate deflection of air into packs are outlined. The importance of face and roadway design features is demonstrated and the consequences of practices inimical to good control of spontaneous combustion are related. Discussions on means of detection and also on the sealant materials available are included.